Las técnicas grafo plásticas en la potenciación de la motricidad fina en segundo grado, de la Escuela “Alonso de Mercadillo”, periodo 2022-2023 - Cordero Zumba, Lelys Daney (2023)
This research work was about grapho-plastic techniques in the potentiation of fine motor skills, worked with the following general objective: To determine the influence of grapho plastic techniques in the potentiation of fine motor skills with students of second grade at "Alonso de Mercadillo" during the 2022-2023 school year. To carry out this study, a descriptive type of research was used, with a quantitative-qualitative approach and quasi-experimental design. During the research process, the methods used in this report of the curricular integration work were: scientific, documentary, hermeneutic, synthetic, analytical, statistical and descriptive. The techniques and instruments used were: the interview applied to the teacher and a test applied to the students, these tools contributed to the data collection in a high level, the research population was "Alonso de Mercadillo" School, 27 students and one teacher were selected through a non-probabilistic sampling, in order to clarify the problem investigated, it was determined that the enhancement of grapho-plastic techniques do have a positive influence on fine motor skills for students to develop reading and writing skills, it helped me to share the knowledge through innovative grapho-plastic techniques that contribute the students ́ learning, managing to stimulate the development of the neuro-musculature in the pre-school age to improve motor activities, this was evidenced with the application of the didactic guide where the different techniques helped students to develop skills, allowing them to strength aspects in the learning process which expresses their feelings, attitudes and ideas through manual activities while improving reading-writing skills. Key words: fine motor skills, teaching - learning, literacy, empowerment, grapho-plastic techniques.